A Cross-Cultural Sequential Model of the Association Between Young Spanish and Colombian Women Victims of Power Imbalance and Suicide Risk: The Mediating Role of Dating Violence and Rumination - Gracia-Leiva, Marcela (Journal of interpersonal violence, 2023)
For young women, the power imbalance in favor of males in dating relationships has been related to dating violence (DV) victimization. In addition, the use of rumination to cope with DV may increase their psychological distress. The purpose of the current study was to examine whether experiences of DV and rumination mediate the association between power imbalance and suicide risk (SR). The sample comprised 1,216 young women aged between 18 and 28 years from Colombia (n = 461) and Spain (n = 755), in a heterosexual dating relationship, not married or cohabiting with a partner and without children. The following scales were applied: The Sexual Relationship Power Scale-Modified, The Dating Violence Questionnaire–-R (DVQ-R); Cyberdating Abuse Questionnaire, Measure of Affect Regulation Scale (MARS), and The Spanish Suicide Risk Scale. A sequential mediation paths model was tested. Results indicated that power imbalance was associated with DV victimization. Furthermore, DV was associated with more rumination, which was also linked to a greater SR in both countries. Rumination may be a mechanism through which experiences of DV victimization negatively influence mental health in young women and is an important variable related cross-culturally to SR. The findings suggest an equality approach, addressing the power imbalance in dating relationships, empowering girls to prevent DV, and teaching coping strategies for dealing with victimization and its consequences.